The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1093/mutage/gep003
|View full text |Cite
|
Sign up to set email alerts
|

In vivo genotoxicity assessment of aluminium oxide nanomaterials in rat peripheral blood cells using the comet assay and micronucleus test

Abstract: Advances in nanotechnology and its usage in various fields have led to the exposure of humans to engineered nanomaterials (NMs) and there is a need to tackle the potential human health effects before these materials are fully exploited. The main purpose of the current study was to assess whether aluminium oxide NMs (Al(2)O(3)-30 nm and Al(2)O(3)-40 nm) could cause potential genotoxic effects in vivo. Characterization of Al(2)O(3)-30 nm and Al(2)O(3)-40 nm was done with transmission electron microscopy, dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(98 citation statements)
references
References 37 publications
2
95
0
1
Order By: Relevance
“…The results from the study indicated a decrease in the cell viability [134]. Another study investigated the effect of increasing concentration of aluminium nanoparticles on rat blood cells at 500-2000 mg/kg for 72 h. It was observed from the study that the toxicity was dose dependent [135]. A study conducted on mammalian cell lines suggested that at 0-5000 μg/mL, aluminium nanoparticles were responsible for DNA damage after treatment for 2 h [136].…”
Section: Effects On Cell Linesmentioning
confidence: 99%
“…The results from the study indicated a decrease in the cell viability [134]. Another study investigated the effect of increasing concentration of aluminium nanoparticles on rat blood cells at 500-2000 mg/kg for 72 h. It was observed from the study that the toxicity was dose dependent [135]. A study conducted on mammalian cell lines suggested that at 0-5000 μg/mL, aluminium nanoparticles were responsible for DNA damage after treatment for 2 h [136].…”
Section: Effects On Cell Linesmentioning
confidence: 99%
“…Al2O3 and TiO2 nanoparticles have reported with internalization and cytotoxicity in CHO cells where it has been shown to induce vesicle formation and got trapped inside the vesicles along with free nanoparticles observed inside the cell (DiVirgilio et al, 2010). It is believed that nanoparticles with smaller size can easily enter into the biological system and the resulting cytotoxicity or genotoxicity is size-dependent (Balasubramanyam et al, 2009). However, titanium dioxide nanoparticles even in range of 150 nm can also internalized and elicit toxic responses as DNA damage and genetic instability (Trouiller et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…DNA damage was evaluated by a comet assay, which was performed according to the published protocol with minor modifications (Balasubramanyam et al, 2009). Briefly, 200 ml of low-melting agarose [1% (v/v) in phosphatebuffered saline (PBS, pH 7.4)] at 37 C mixed with 10 ml of PBS containing MNCs was transferred onto a precoated [0.5% (v/v) normal melting agarose in PBS (pH 7.4)] slide.…”
Section: Comet Assaymentioning
confidence: 99%